Design and fabricate walkingaided tool for paralyzed people - Abdul Rashid, Muhammad (2008)
Designing and fabricating a walking aided tool is a product to fulfill customer needs especially for those who are half paralyzed people for rehabilitation process or move in their daily activities better. Overall, this project involves with many processes, starting from designing the concept of the product, fabrication process which involves with some mechanical process such as machining, welding, drilling and other process.There are several aspects which are considered on this project such as high strength, ergonomic and other. Material used on this project consist of hollow steel tube, hollow steel pipe and steel bar in order to support certain weight capacity. This product also built with specific height in order to meet the ergonomic aspect to make the user comfortable and the product users friendly. Even though there are a lot of existing products on the market, the completion of this model provides a more practical usage.